Organizing Management of Early Childhood Education Institution: A Case Study at One Raudhatul Athfal in Palembang - Leny Marlina (Ta'dib: Jurnal Pendidikan Islam, 2021)
This study aimed to analyze the organizing management of early childhood education at one Raudhatul Athfal in Palembang, especially the input component as an effort to improve and develop the management of the institution. This study used qualitative case study research with inductive logic of thinking to analyze about the situation or meaning of the characteristics of the object under study. The main informant was the principal of Raudhatul Athfal and the supporting informants were teachers, parents and the school committee. Data collection techniques were conducted by doing observation, interviews, and documentation. Meanwhile, the data analysis technique followed the flow model (data reduction, data display, and data verification). The results showed that the organizing management at the Raudhatul Athfal especially on the input components (school vision and mission, goals, human resources (students and teachers)), curriculum, facilities, infrastructure (equipment, and equipment) and financing had been carried out, although there were still things that needed to be addressed, such as the recruitment system of teacher which was not yet systematic. In this study, the researcher saw that in addition to the management of organizing inputs, other factors that influenced the development and progress of this institution were the management system that was less clear from the foundation, where management of some school activities or programs were already independent, but for the procurement of needs or costs of activities they were still not independent because they had to coordinate first so that the school was less flexible. In other words, the school needed a common vision of all members starting from foundation managers, school principals, as well as teachers and students.